ANALISIS ASUHAN KEPERAWATAN PENGGUNAAN KARTU PINTAR DAN GELAS UKUR TERHADAP INTERDYALISIS WEIGHT GAIN (IDWG) PADA PASIEN HEMODIALISA - Peren Dita Sanli (2022)
The degree to which a patient adheres to the advice given by a doctor or other individual to achieve a goal is referred to as compliance. Edema is an excessive accumulation of fluid between body cells or in various body cavities, while IDWG is an increase in fluid volume with an increase in body weight as a basis for determining the amount of fluid that enters during the interdialytic period. The application of the results of this study aims to determine the effect of using smart cards and measuring cups on the Interdialytic Weight Gain (IDWG) of hemodialysis patients. The application of the results of this study was applied to patients with chronic kidney failure in the Hemodialysis Room of the Police Hospital Said Sukanto. The application of the use of smart cards and measuring cups was carried out for 4 consecutive days with 2 meetings. Based on the results of the application of smart cards and measuring cups in managed patients, it was shown that there was a decrease in IDWG levels from 6.5% to 3.3%. Meanwhile, in resume patients who were not given smart card intervention, there was a change in the IDWG value from 6.1% to 4.1%. These results show that the use of smart cards and measuring cups is effective in limiting fluids in patients with chronic kidney failure. It is recommended for health workers to continue to provide education and interventions using smart cards and measuring cups in patients with chronic kidney failure.